Autonomy-hindering scope for physiotherapy practice in African countries: Results of creatures and antinomies of regulatory laws - Ushotanefe Useh (AOSIS, 2021)
Background: Healthcare professionals in different countries are governed by laws and statutes for their scopes of practice to ensure that services are rendered by suitably licenced and qualified professionals in order to protect the public. A few of these laws are found to paradoxically hinder the autonomy of physiotherapy. Objective: My article documents the autonomy-hindering scope for physiotherapy practice in selected African countries. Method: The methodologies used in my article were both a review and comparative approach for the interpretation of statutes. Results: Three African countries presented a clear legal definition of physiotherapy in their regulatory frameworks and regulated other rehabilitation professions as well. In my article, these regulations are referred to as 'combo regulations'. The rationale for 'combo regulations' is not clear and found to hinder professional autonomy. Only one statute from Rwanda provided a scope for physiotherapy that was not autonomy-hindering. Conclusion: There is, therefore, a need for urgent review of most laws regulating physiotherapy in the selected African countries to assist with the duty of protecting the public. All autonomy-hindering scopes for physiotherapy practice in African countries should be repealed and amended accordingly. Clinical implications: A clear scope shall assist with protecting the public and clinical practice and clearly states 'what physiotherapy is and what it is not'.